Awareness of gestational diabetes mellitus among pregnant women attending a government hospital - Rai, Melina; Chaudhary, Tanuja Kumari (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Gestational Diabetes Mellitus (GDM) is a common metabolic disorder in pregnancy associated with significant maternal and neonatal complications. Low awareness among pregnant women increases health risks for both mother and child. Assessing awareness can promote better self-care, prevention, and management. This study aimed to evaluate awareness of gestational diabetes mellitus among pregnant women attending a government hospital. Materials and Methods: A cross-sectional study design was adopted. Non-probability purposive sampling technique was used to collect data among 100 pregnant women who met the inclusion criteria. Self-developed structured interview schedule was used to collect the data. Data processing was done by using Statistical Package for Social Science version 16. Both descriptive and inferential statistics were used in the study. In descriptive statistics, number, percentage, mean and standard deviation were used to describe socio-demographic, obstetric and maternal variables. In inferential statistics, Chi square test was used to find out the association between dependent and independent variables. Results: The finding of this study showed that nearly one third of the respondents (30.0%) had good level of awareness on Gestational Diabetes Mellitus while 48.0% of respondents had moderate level of awareness and 22.0% of respondents had less awareness. Gravida was statistically significant relationship between awareness level of Gestational Diabetes Mellitus. Conclusions: This study concluded that awareness regarding Gestational Diabetes Mellitus was higher in most of the pregnant women and health personnel were identified as the primary source of information. These findings emphasized the need for targeted interventions to enhance awareness on Gestational Diabetes Mellitus.